2008
DOI: 10.1097/wno.0b013e318175cd90
|View full text |Cite
|
Sign up to set email alerts
|

Asymptomatic Peripapillary Subretinal Hemorrhage: A Study of 10 Cases

Abstract: We have described a benign syndrome of isolated PSH in crowded and tilted optic discs in myopic eyes of white women. The PSHs do not cause visual symptoms and resolve spontaneously. We propose that an interplay of ocular motor forces, scleral thinning, and vitreopapillary traction acting on a morphologically vulnerable optic disc explains these hemorrhages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
39
2
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 30 publications
6
39
2
1
Order By: Relevance
“…The complexity of physiological eye movements (e.g., combination of adduction and depression) in association with variations in eye and orbit anatomy (e.g., axial length or location of the optic nerve origin in the nasal upper region of the orbit) may contribute to the variety of tilting directions seen in patients with tilted optic discs. 43 Additionally, Sibony et al 44 reported that patients with myopic tilted discs may spontaneously develop peripapillary subretinal hemorrhages. The authors speculated that these were caused by gaze-evoked shearing of blood vessels at the ONH site.…”
Section: Discussionmentioning
confidence: 99%
“…The complexity of physiological eye movements (e.g., combination of adduction and depression) in association with variations in eye and orbit anatomy (e.g., axial length or location of the optic nerve origin in the nasal upper region of the orbit) may contribute to the variety of tilting directions seen in patients with tilted optic discs. 43 Additionally, Sibony et al 44 reported that patients with myopic tilted discs may spontaneously develop peripapillary subretinal hemorrhages. The authors speculated that these were caused by gaze-evoked shearing of blood vessels at the ONH site.…”
Section: Discussionmentioning
confidence: 99%
“…When VH occurs in young patients, vitreopapillary traction appears to play an important role in the genesis of the peripapillary subretinal hemorrhages [10]. However, there were some patients who had a SRH without a posterior vitreous detachment [11]. Two of our patients had a ruptured macroaneurysm at the optic disc, but did not have peripapillary subretinal hemorrhages and a posterior vitreous detachment.…”
Section: Discussionmentioning
confidence: 98%
“…If there is no history of hypertension and diabetes mellitus, it is necessary to determine the cause in other congenital retinal vascular anomalies such as collagen disease, Coats’ disease, Leber's miliary aneurysms, and von Hippel-Lindau diseases [3, 10, 11, 12, 13, 14]. In addition, we must rule out granulomatous diseases such as sarcoidosis, toxoplasmosis, and tuberculosis, which can also produce a mass on the optic disc [14].…”
Section: Discussionmentioning
confidence: 99%
“…Eğik diskle birlikte nadir olarak görülen bu kanamaların sebebinin, skleradaki incelme ve vitre ile makula arasındaki traksiyon olduğu ileri sürülmüştür. 27,28 Eğik diskin optik disk druseni ile olan birlikteliği literatürde nadir olarak bildirilmiş olup, aralarındaki ilişki hâlen tam olarak açıklanamamıştır. Eğik diskte skleral kanalda oluşan sıkışıklığın aksoplazmanın dengesini bozarak drusenin gelişimine sebep olduğu öne sürülmüştür.…”
Section: Kli̇ni̇k Bulgularunclassified